2016
DOI: 10.1111/ssqu.12351
|View full text |Cite
|
Sign up to set email alerts
|

Who's on the Bench? The Impact of Latino Descriptive Representation on U.S. Supreme Court Approval Among Latinos and Anglos*

Abstract: Objectives Few studies have examined the impact of the descriptive representation of Latinos on evaluations of the judiciary. This study helps to fill that gap by examining the effect of the appointment of Sonia Sotomayor on Latinos’ and Anglos’ evaluations of the U.S. Supreme Court. Methods Using repeated measures from surveys conducted in Texas in 2006 and 2011, we use ordered logit analysis to estimate the impact of the Sotomayor appointment on approval of the U.S. Supreme Court among Latinos and Anglos. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…These findings are consistent with the particularistic mobility thesis of institutional trust (Klugman and Xu, 2008; Wilson, 1997), which suggests that groups with little societal privilege trust more in institutions that can help facilitate their social mobility. Conversely, our findings are inconsistent with the theory of descriptive representation (Sanchez and Morin, 2011; Fowler, Merolla, and Sellers, 2014; Evans et al., 2017), since women and racial minorities are underrepresented in Congress. Whether or not Congress has been effective at leveling the playing field, our findings suggest that underprivileged groups recognized it as a potentially democratizing institution at this particular moment in time.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with the particularistic mobility thesis of institutional trust (Klugman and Xu, 2008; Wilson, 1997), which suggests that groups with little societal privilege trust more in institutions that can help facilitate their social mobility. Conversely, our findings are inconsistent with the theory of descriptive representation (Sanchez and Morin, 2011; Fowler, Merolla, and Sellers, 2014; Evans et al., 2017), since women and racial minorities are underrepresented in Congress. Whether or not Congress has been effective at leveling the playing field, our findings suggest that underprivileged groups recognized it as a potentially democratizing institution at this particular moment in time.…”
Section: Discussioncontrasting
confidence: 99%
“…Our primary social location variables of interest were gender and racial‐ethnic status, as both are consistently associated with institutional trust (Evans et al., 2017; Wilkes and Wu, 2018). For gender, we created a dichotomous measure indicating whether the respondent identified as female (1) or male (0).…”
Section: Methodsmentioning
confidence: 99%
“…We are particularly attentive to relevant counterfactuals and the generalizability of our findings. Research designs such as those used in Badas and Stauffer (2018) and Evans et al (2017) are not well-suited for identifying whether shared race and/or gender affected support for those nominees differently than an otherwise-similar nominee with different descriptive characteristics. 9 9The lack of exogeneity also makes it difficult to evaluate the interaction between ideological proximity and shared race and/or gender, as respondents' perceptions of nominee ideology are likely subject to projection effects.…”
Section: Descriptive Representation and Public Support For Judicial Nomineesmentioning
confidence: 99%
“…The omission is especially surprising due to the importance politicians, political observers, interest groups, and the public have placed on the confirmation of nominees from underrepresented groups to the Supreme Court in recent decades, including Sandra Day O'Connor, Clarence Thomas, Ruth Bader Ginsburg, Sonia Sotomayor, and Elena Kagan. While substantial literature studies how descriptive representation affects attitudes toward legislatures (e.g., Gay, 2002; Schwindt-Bayer and Mishler, 2005; Preuhs, 2006) and executives (e.g., Atkeson and Carrillo, 2007; Merolla et al , 2013), strikingly little is known about how the demographic attributes of judges and judicial nominees affect public attitudes toward them (see, however, Evans et al , 2017; Badas and Stauffer, 2018).…”
Section: Demographic Representation and The Judiciarymentioning
confidence: 99%
“…For example, one study found that awareness of the Supreme Court among Latinos in the United States increased following Justice Sonia Sotomayor's appointment to the Supreme Court in May 2009. 36 In addition to studies examining public awareness of the Supreme Court, there are a few studies that have examined public awareness of the lower courts in the United States. Sara Benesh, Nancy Scherer and Amy Steigerwalt found that only about one-quarter of participants in a survey that they administered knew how Federal judges were appointed, although this figure is slightly higher when 'nearly correct' answers are included.…”
Section: Existing Studiesmentioning
confidence: 99%